PENGARUH KUALITAS PELAYANAN ADMINISTRASI PADA PROGRAM STUDI TERHADAP KEPUASAN MAHASISWA PRODI ADMINISTRASI PUBLIK UNIVERSITAS MUHAMMADIYAH SIDENRENG RAPPANG - Ermi, Nurindah Wardani; Sapri; Mannu, H. Ahmad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to determine the influence of the quality of study program administrative services on student satisfaction at the Public Administration Study Program at Muhammadiyah University of Sidenreng Rappang. The research employs a descriptive quantitative approach. The population consisted of active students from the 2021 to 2024 cohorts, with a sample of 80 respondents. Data were collected using questionnaires, observation, and literature review. The data were analyzed using descriptive statistics and simple linear regression with SPSS sversion 25. The results show that the quality of administrative services is in the good to very good category, based on five service dimensions: tangibles (85%), reliability (87.5%), responsiveness (91.25%), assurance, and empathy. Student satisfaction is also categorized as very good, with indicators such as product quality (92.5%), service quality (91.25%), emotional factors (88.75%), price factors (92.5%), and cost and convenience (87.5%). The regression test results indicate that the t-value (14.393) is greater than the t-table (1.990) and the significance value is 0.000 < 0.05, which means there is a significant and positive influence between the quality of administrative services and student satisfaction. The R Square value of 0.726 indicates that 73% of the variation in student satisfaction is influenced by administrative service quality, while the remaining 27% is influenced by other factors.